Pengaruh smartphone terhadap interaksi mahasantri Ma’had Sunan Ampel Al Aly: Observasi pada mahasantri Mabna Khadijah Al Kubra kamar 21 - Anggraeni, Selvi (Maliki Interdisciplinary Journal, 2023)
This study examines the implications and role of smartphones in modern life, especially in Indonesia. Smartphones are sophisticated handheld telecommunications devices with a variety of features and utilities, and have a significant influence on various aspects of life. The positive effects include ease of access to information via the internet, remote communication, and entertainment. Even so, excessive use can potentially lead to negative impacts such as health problems and sleep disorders. This research also reviews the use of smartphones by students and students, along with their effects on social interaction. Reduced social interaction can result in isolation and difficulty communicating in real life. Prevention efforts and awareness in using smartphones were identified as the main factors in overcoming their negative impacts. By understanding the positive and negative effects of smartphones, and applying self-control in their use, people can reduce the adverse effects arising from this technology. In the context of mahasantri, managing smartphone use is one of the solutions to overcome negative effects and promote healthy social interaction.